RBM10‐TFE3 fusions: A FISH‐concealed anomaly in adult renal cell carcinomas displaying a variety of morphological and genomic features: Comprehensive study of six novel cases. Issue 11 (6th August 2021) - Di Mauro, Ilaria; Dadone‐Montaudie, Bérengère; Sibony, Mathilde; Ambrosetti, Damien; Molinie, Vincent; Decaussin‐Petrucci, Myriam; Bland, Vincent; Arbaud, Claire; Cenciu, Béatrice; Arbib, François; Just, Pierre‐Alexandre; Derman, Jonathan; et al.
Abstract: The accurate diagnosis of Xp11‐translocation renal cell carcinoma (RCC) in adults is challenging. TFE3 (located on chromosome X) fuses with a partner gene generally located on another chromosome. In rare cases TFE3 may fuse with a neighboring gene: RBM10 . Because TFE3 false‐positive immunostaining is a common pitfall in many laboratories, demonstration of the chromosomal rearrangement is required in order to ascertain the diagnosis. Fluorescence in situ hybridization (FISH)—that has been considered as the gold standard method—reaches its limits for detecting small Xp11 paracentric inversions. We performed a comprehensive clinical, histological and genomic study of six novel cases of RCC with RBM10‐TFE3 fusion. Using FISH, TFE3 rearrangement was equivocal in one case and negative in others. RBM10‐TFE3 fusion was discovered using targeted RNA sequencing (RNASeq). As all the previously reported cases (mean age: 50), the six patients were adults (mean age: 42), suggesting an epidemiologic difference between RBM10‐TFE3 RCC and tumors harboring some other partner genes, such as ASPSCR1 that rather occur in children. Array‐comparative genomic hybridization showed several alterations, notably a gain of 17q in four cases with papillary features and loss of 3p in one case with clear cells. Our study demonstrates that, though rare among adult cases of RCC, RBM10‐TFE3 fusion is not exceptional and warrants appropriate molecular detection. Notably, it would be worthy to systemically investigate by RNASeq challenging RCC with type‐2 papillary features and 17q gain.